Caregivers' views on stigmatization and discrimination of people affected by leprosy in Ghana. - Emmanuel Asampong; Mavis Dako-Gyeke; Razak Oduro (Public Library of Science (PLoS), 2018)
Leprosy is a condition that has long been associated with stigma and discrimination, even when infected persons have been cured. This paper describes stigma and discrimination as viewed by caregivers who are associated with people affected by leprosy in Ghana.A qualitative interview with semi-structured interviews were conducted for twenty caregivers.Findings indicated that caregivers were of the view that people affected by leprosy in Ghana are stigmatized and discriminated against by the larger society thus making their movements and interactions restricted to the Leprosarium. Besides, employments opportunities are unavailable to them thus making them exposed to financial challenges. The livelihood Empowerment Against poverty (LEAP) money given them is not sufficient for their daily upkeep.People affected by leprosy in Ghana are stigmatized and therefore find it difficult to interact freely with the public. The associated physical deformities with the disease also tend to impede their ability to relate to the general public. The LEAP cash given to people affected by leprosy is helpful however, it could be enhanced to keep pace with prevailing economic conditions in the country.